Penguatan Resiliensi Remaja sebagai Upaya Preventif Penyimpangan Sosial melalui Sarasehan dan Workshop di Desa Sidoarum, Sleman, Yogyakarta - Aris Martiana; Dwi Agustina; Datu Jatmiko (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Kupang, 2026)
Adolescents are a group vulnerable to deviant behavior due to the influence of their social environment, family, and technological advancements. Therefore, efforts are needed to strengthen their resilience as an adaptive capacity to cope with life’s pressures and challenges. This community service activity aims to strengthen adolescents’ resilience to minimize social deviance in Sidoarum Village, Sleman, Yogyakarta. The method used is a participatory descriptive approach through the stages of needs analysis, planning, implementation, and evaluation. The activities were conducted in the form of forums and workshops involving adolescents, parents, village officials, and the community. The results of the activities indicate an increase in participants’ understanding of the forms, causal factors, and impacts of social deviance, as well as the importance of resilience in managing social pressures and negative environmental influences. Furthermore, it was found that the roles of families, the community, and village institutions are crucial in supporting the development of adolescent resilience. This program also promotes awareness of the importance of providing positive activities for adolescents. Thus, strengthening resilience has proven effective as a preventive measure to minimize social deviance and enhance adolescents’ social resilience.